O romance estilhaçado: La vida en las ventanas, de Andrés Neuman e Berkeley em Bellagio, de João Gilberto Noll - Melo, Ivana Ferigolo (2013)
From the second half of the twentieth century, the West starts to record significant changes in the social, political, economic, ideological and cultural sphere. For many scholars/researchers, one of the central consequences of these changes is the consolidation of a globalized world, borders and national identities weakened or dissolved and lacking in grand narratives of utopian nature and homogenizing. Such globalized reality seems to resonate in the instance of cultural production and thus literary. One of the signs of this impact tends to be the appearance of certain narratives, to distance themselves from the most expressive modalities expressed by romance throughout modernity, requesting literary criticism defining new parameters for analysis and interpretation. Two examples, among others, of reports that seem to show a large gap in relation to expressions of romance in modernity are La vida en las Ventanas, the Spanish-Argentine writer Andrés Neuman and Berkeley in Bellagio, the author João Gilberto Noll. Assuming that these narratives present ties to the social, existential and spiritual atmosphere that is drawn in the West, from the second half of the last century, this work seeks to clarify, from the analysis of both narratives, that the understanding of the cultural and aesthetic sense of these reports depends on the definition of parameters differentiated analysis and interpretation of which were developed throughout modernity to the romance genre. In this sense, the work is structured from the review of relevant placements of literary criticism in Spain and Brazil today; recovery of the novel theories elaborated by authors such as Lukacs, Feher, Bakhtin, among others, and the review and discussion the thought of authors who try to explain the peculiarities of Western historical phase following the second world war, as Vattimo, Jameson, Anderson, Habermas, Lasch, etc.. It is concluded from the analysis of the works that the motives that drive the contemporary novelistic creation differ from that motivated formalization throughout modernity, the romance factor that leads to formal register modifications and requiring other analytical and interpretive devices.